IMF Survey, Volume 36 Issue 06. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
Spring Meetings preview, world outlook, global financial stability, U.S. subprime mortgages, labor globalization, external imbalances, IMF and Africa, wage bill ceilings, policy support instrument, modernizing IMF surveillance, India, Bulgaria, PNoWB.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet